Growing enough food without enough water - David, S. (CAB International, 2011)
Water scarcity is already a reality. More food will be required for a growing and wealthier and urbanized population that will put more pressure on water resources. With several water-related limits reached or breached - groundwater decline, shrinking rivers and threatened fisheries - we must ask, 'Will there be enough water to grow enough food? It is possible to produce the food needed, but if present practices continue it is not probable that we will solve the many poverty and environmental challenges confronting us. To share a scarce resource and to limit environmental damage in the face of climate change, it is imperative to limit future water use. Important pathways to growing enough food with limited water are to increase productivity of water in irrigated and rainfed areas, improve water management in low-yielding rainfed areas, and to consider our own food consumption patterns. In pockets of poverty in Sub-Saharan Africa and Asia, expanding access to water through a range of water management solutions holds the key to food security and poverty reduction. For sustainable water use, water managers must consider agriculture as an ecosystem and how other ecosystem services are impacted through water. These actions will require serious changes in how we think about water and food, and how we govern water and land resources.